Productivity, Nutrient Composition, and Hydrocyanic Acid Concentration of Super-2 Forage Sorghum at Different NPK Levels and Planting Spaces - Astuti, D.; Suhartanto, B.; Umami, N.; Irawan, A. (Tropical Animal Science Journal, 2019)
Low digestibility and toxicity of hydrocyanic acid (HCN) in sorghum forage are disadvantage for ruminant. Appropriate fertilizer application and planting strategy can improve sorghum yield and quality. A field experiment was aimed to investigate the productivity, nutrients content, and HCN concentration of Super-2 forage sorghum (Sorghum bicolor (L) Moench) at different planting spaces and levels of NPK fertilizer. The seeds were planted according to 3×3 factorial design in which the first factor was planting space (J1= 90×20 cm, J2= 75×25 cm, and J3= 60×30 cm) and the second factor was three levels of NPK fertilizer (P1= 0 kg/ha; P2= 100 kg/ha; and P3= 200 kg/ha, respectively). Crude protein (CP), crude fiber (CF), and HCN concentration were affected by the interaction of NPK levels × planting spaces (p